A Modified Reverse Remplissage Procedure for Management of a Locked Posterior Shoulder Dislocation - Xavier Zwiebel; Stéphane Pelet; Alexandre Leclerc (Case Reports in Orthopedics)
Posterior shoulder dislocation is rare and often represents a diagnostic and therapeutic challenge. An impaction fracture of the anteroinferior aspect of the humeral head (called a reverse Hill-Sachs (RHS) fracture) is always present in case of chronic locked posterior dislocation. Surgical management is required and decided on the delay between the trauma and the diagnosis and the importance of the RHS (in percentage). The authors present a chronic locked posterior shoulder dislocation in a 32-year-old active male with a reverse Hill-Sachs lesion of more than 40%. An open reduction was required, and stabilization was achieved with a modified remplissage technique with detachment of the upper quarter of the subscapularis tendon. Three years after the surgery, the patient recovered an excellent functional level with a stable shoulder.